Safety and Efficacy of Intravenous Iron Sucrose versus Low Molecular Weight Iron Dextran for Treatment of Iron Deficiency Anemia in Pregnancy: A Randomized Controlled Trial - Samsudin, Sarah (Int J Womens Health, 2020)
OBJECTIVE: This study aimed to compare the efficacy, side effects, and clinical outcomes between parenteral iron sucrose complex (ISC) and low-molecular-weight iron dextran (LMWID) for iron deficiency anemia (IDA) in pregnancy. METHODS: The study was conducted in a Malaysian tertiary hospital for a period of 1 year. Forty pregnant women with IDA between 24 and 38 weeks of gestation were randomized into two groups receiving treatment with either ISC or LMWID. RESULTS: No significant difference was found between the groups in terms of demographic data, parity, and mean gestational age. A mean total of 835 ± 150 mg doses of ISC and 656 ± 382 mg doses of LMWID were administered (P = 0.0001). Adverse events were reported in five patients who received LMWID and none in those treated with ISC (P = 0.024). The mean hemoglobin (Hb) level increment 2 weeks post treatment was higher among those who received ISC than in those who received LMWID. The ISC group demonstrated an increase of 1.91 ± 1.10 g/dL (from 8.43 ± 1.03 g/dL to 10.29 ± 0.90 g/dL) compared with the LMWID group at 1.39 ± 0.54 g/dL (from 8.61 ± 0.70 g/dL to 9.92 ± 0.88 g/dL, P = 0.023). All participants in both groups delivered at term. The estimated blood loss during delivery was significantly higher in the LMWID group (359 ± 247 mL) than in the ISC group (280 ± 100 mL, P = 0.026). Otherwise, no significant difference was observed in terms of Hb level during delivery and the perinatal outcomes for both groups. CONCLUSION: Parenteral ISC is more effective than LMWID in treating maternal IDA, and it is associated with fewer adverse events.